Value-driving activities in Euro-zone banks - Isidro, H.; Grilo, D. (European Accounting Review, 2012)
Wedevelop and test accounting-based valuationmodels for commercial banks. WeextendBegley et al.’s framework (2006) and propose a valuationmodelwhere goodwill is generated by virtually all commercial and investment banking activities. Key features of our model are: the development of a relation between future cash flows from fee income and the bank value that depends on lending, borrowing and off-balance sheet business; and the inclusion of proprietary investment and trading as value-driving activities. Empirical tests on a sample of Euro-zone banks from 1998 to 2006 provide the following evidence. Unrealised expected cash flows from fee income are the most important source of unrecorded goodwill. This is consistent with the increasing importance of revenue from the sale of financial services to banks’ income. The contribution of fee income to goodwill is higher for banks with large deposits and new loans. Equity securities are a source of unrecorded goodwill, but the introduction of fair value accounting, with the adoption of the International Financial Reporting Standards (IFRS), reduces their valuation role. Yet equity securities remain positively associated with unrecorded goodwill after IFRS adoption, suggesting that the fair value standards do not fully capture market expectations about future cash flows of investment assets.